(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Germline gene editing technologies are rapidly spreading all over the world. Therefore, there is a strong need for the law to start regulating the matter, because of the improvement of the CRISPR/Cas-9 technique and the possible risks involved. The present article aims to analyse under a comparative perspective whether it is possible to consider a hypothetical right to be born with a genetic inheritance not (arbitrarily) modified as a reason for an absolute ban on these techniques.